EDUCATION CURRICULUM FOR SOCIETY 5.0 IN THE NEXT DECADE - Usmaedi, Usmaedi (STKIP Setiabudhi, 2021)
Industry 4.0 has become a major revolution in the development of human life. Digital technology has influenced humans in various ways from economic, social, political and even in human life itself. Society 5.0 places more emphasis on efforts to place humans as the center of innovation (human centered) while technological advances are utilized to improve the quality of life, social responsibility and develop sustainability. This research is a qualitative research with literature study method. This method collects information or data through books, journals or articles that are relevant to the issue being studied. Society 5.0 emerged as a development of the industrial revolution 4.0 which was considered to have the potential to degrade the role of humans themselves. In society 5.0, humans will be the center (human centered) while remaining technology-based. The emergence of society 5.0 requires patented breakthroughs in an effort to face the challenges that will be posed by society 5.0. The existence of society 5.0 poses its own challenges in various fields of life, one of which is in the field of education, including learning. To deal with the complexities of living conditions in the Society 5.0 era, students are not sufficiently equipped with the ability to read, write and count or better known as